Dietary molasses increases ruminal pH and enhances ruminal biohydrogenation during milk fat depression - Evan C. Titgemeyer; Barry J. Bradford (Kansas Agricultural Experiment Station Research Reports, 2009)
Molasses has long been used in animal feeds for palatability and as a binding agent to ensure uniform consumption of essential nutrients. Recent work with molasses in highly fermentable diets has revealed that molasses might offer additional benefits in dairy rations. Feeding highconcentrate diets increases the risk of milk fat depression by disrupting the normal pathway of fatty acid biohydrogenation in the rumen. Preliminary research conducted at Kansas State University and other universities has indicated that dietary sugars have the potential to increase milk fat synthesis during milk fat depression. In this study, we sought to understand the reasons for this beneficial effect of molasses on milk fat synthesis. Despite the fact that molasses provides readily fermentable sugar, replacing 5% of dietary corn grain with molasses increased ruminal pH, improved fatty acid biohydrogenation, and shifted the profile of fermentation acids in a manner suggesting that growth of fiber-digesting bacteria was improved. Results of several studies suggest that 5% dietary molasses can increase milk fat yield by 5 to 10%, and the current study indicates that this effect is driven by a stabilization of ruminal pH and biohydrogenation; Dairy Day, 2009, Kansas State University, Manhattan, KS, 2009; Dairy Research, 2009 is known as Dairy Day, 2009
Keywords: Kansas Agricultural Experiment Station contribution; no. 10-103-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1021; Dairy Day; 2009; Dairy; Feed intake; Milk fatty acids; Milk yield; Molasses; Rumen pH